Social tagging within task management - Vadangi, Anil Raj (My University, 2011)
Social tagging evolved in response to a need to tag heterogeneous objects, the automated tagging of which is usually not feasible by current technological means. Social tagging can be used for more flexible competence management within organizations. The profiles of employees can be built in the form of groups of tags, as employees tag each other, based on their familiarity of each other’s expertise. This can serve as a replacement for the more traditional competence management approaches, which usually become outdated due to social and organizational hurdles, and obsolete data. These limitations can be overcome by people tagging, as the information revealed by such tags is usually based on most recent employee interaction and knowledge. Task management as part of personal information management aims at the support of users’ individual task handling. This can include collaborating with other individuals, sharing one’s knowledge, both functional and process-related, and distributing documents and web resources. In this context, Task patterns can be used as templates that collect information and experience around tasks associated to it during run time, facilitating agility. The effective collaboration among contributors necessitates the means to find the appropriate individuals to work with on the task, and this can be made possible by using social tagging to describe individual competencies. The goal of this study is to support finding and tagging people within task management, through the effective exploitation of the work/task context. This involves the utilization of knowledge of the workers’ expertise, nature of the task/task pattern and information available from the documents and web resources attached to the task. Vice versa, task management provides an excellent environment for social tagging due to the task context that already provides suitable tags. The study also aims at assisting users of the task management solution with the collaborative construction of light-weight ontology by inferring semantic relations between tags. The thesis project aims at an implementation of people finding & tagging within the java application for task management that consumes web services, which provide the required ontology for the organization.
Smart social tagging support for task management through work context exploitation